Kynurenic Acid Content in Selected Culinary Herbs and Spices - Michal P. Turski; Monika Turska; Tomasz Kocki; Waldemar A. Turski; Piotr Paluszkiewicz (Journal of Chemistry)
Previous studies demonstrated that kynurenic acid (KYNA) is present in various types of food in varying concentrations. Therefore, the aim of the study was to check whether KYNA is present in culinary herbs and spices. Achieved results indicate that KYNA is present in all 19 selected culinary herbs and spices. The highest concentration of KYNA was found in basil and thyme, 14.08 and 8.87 μg/g, respectively, while the lowest content of KYNA was found in cumin and black pepper, 0.64 and 0.10 μg/g, respectively. This is the first report on the concentration of KYNA in culinary herbs and spices. The need for more detailed investigation of dietary supplementation with culinary herbs and spices containing KYNA is suggested.